Trans-corneal drug delivery strategies in the treatment of ocular diseases - Li, Liping; Jia, Fan; Wang, Youxiang; Liu, Jiamin; Tian, Yi; Sun, Xinghuai; Lei, Yuan; Ji, Jian (Advanced drug delivery reviews, 2023)
[Display omitted] The cornea is a remarkable tissue that possesses specialized structures designed to safeguard the eye against foreign objects. However, its unique properties also make it challenging to deliver drugs in a non-invasive manner. This review highlights recent advancements in achieving highly efficient drug transport across the cornea, focusing on nanomaterials. We have classified these strategies into three main categories based on their mechanisms and have analyzed their success and limitations in a systematic manner. The purpose of this review is to examine potential general principles that could improve drug penetration through the cornea and other natural barriers in the eye. We hope it will inspire the development of more effective drug delivery systems that can better treat ocular diseases.